Divine simplicity: some recent defenses and the prevailing challenge of analogical language. Issue 1 (1st January 2021) - Misiewicz, Rory
ABSTRACT: This essay's aim is to demonstrate how recent defenses of divine simplicity have failed to address the prevailing challenge of analogical language, and thereby render much of their argumentation for simplicity's appropriateness in Christian theology null-and-void. For this task, three book-length works published within the last few years are examined: Steven Duby's Divine Simplicity: A Dogmatic Account (2016), D. Stephen Long's The Perfectly Simple Triune God: Aquinas and His Legacy (2016), and Jordan Barrett's Divine Simplicity: A Biblical and Trinitarian Account (2017). The first section briefly details what each author understands divine simplicity to characterize, and how that characterization involves the pivotal denial of God belonging to any genus. The second section addresses the extent to which each author provides an answer as to how one can analogically speak of a simple God. Finally, the third section critiques the kinds of analogical positions found in Thomas Cajetan's influential De Nominum Analogia, showing that they do not provide a sufficient analogical framework to ground intelligible propositions or inferences about a simple God, which thereby places the original three authors' defenses in danger of serious incoherence.